Recent advances microRNAs and metabolic reprogramming in colorectal cancer research - Xiong, Bin; Huang, Qiaoyi; Zheng, Huida; Lin, Shu; Xu, Jianhua (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) is a cancer with the highest incidence and mortality. Alteration of gene expression is the main pathophysiological mechanism of CRC, which results in disturbed signaling pathways and cellular metabolic processes. MicroRNAs are involved in almost all pathophysiological processes and are correlative with colorectal cancer metabolism, proliferation, and chemotherapy resistance. Metabolic reprogramming, an important feature of cancer, is strongly correlative with the development and prognosis of cancers, including colorectal cancer. MicroRNAs can target enzymes involved in metabolic processes, thus playing a regulatory role in tumor metabolism. The disorder of the signaling pathway is another characteristic of tumor, which induces the occurrence and proliferation of tumors, and is closely correlative with the prognosis and chemotherapy resistance of tumor patients. MicroRNAs can target the components of the signaling pathways to regulate their transduction. Understanding the function of microRNAs in the occurrence and proliferation of CRC provides novel insights into the optimal treatment strategies, prognosis, and development of diagnosis in CRC. This article reviews the relationship between CRC and microRNA expression and hopes to provide new options for the diagnosis and treatment of CRC.